Lamp spectrum and spatial brightness at photopic levels: A basis for developing a metric. (February 2015) - Fotios, S; Atli, D; Cheal, C; Houser, K; Logadóttir, Á
Light sources are available in a variety of spectral power distributions (SPDs) and this affects spatial brightness in a manner not predicted by quantities such as illuminance. Tuning light source SPD to better match the sensitivity of visual perception may allow the same spatial brightness but at lower illuminance with potential reductions in energy consumption. Consideration of experimental design was used to review 70 studies of spatial brightness. Of these, the 19 studies considered to provide credible evidence of SPD effects were used to explore metrics for predicting the effect of SPD but did not provide conclusive evidence of a suitable metric, in part because of incomplete reporting of SPD characteristics. For future work, these data provide an independent database for validating proposed metrics.